HIGH SCHOOL STUDENTS PROFILE OF MISCONCEPTION IN KINETIC THEORY OF GASES - YOPI PUTRA, LINGGA; JATMIKO, BUDI (Inovasi Pendidikan Fisika, 2019)
Misconception is student conceptions that oppose the scientist`s. The purpose of this research was to describe students` profile of misconception on kinetic theory of gases before and after remedial instructions using discussion learning model. This research used pre-experimental design with one-group pre-test post-test design. Subject of this research is 36 science class student in Lamongan, Indonesia. Before the instructions conduct, three-tier diagnostic test formatted pre-test is given to reveal student misconceptions profile. Physic instructions using discussion learning model then conducted. After the instructions, the same diagnostic test formatted was given as post-test. Collected data then analyzed to describe student misconceptions profile before and after the instructions. The result show that before the instructional there are misconception students got as average in every sub-concept, after the instructions, misconceptions was reduced. Keywords: Misconception, Remedial, Kinetic theory of gases.